ANALISIS KUALITATIF PERILAKU KERJA GURU MELALUI OBSERVASI DI SEKOLAH DASAR : STUDI KASUS DI SD NEGERI 11 PANCUNG SOAL - Shalma Wafiq Azizah (Journal of Cultural and Innovative Education, 2026)
This qualitative study analyzes teachers' work behavior at SD Negeri 11 Pancung Soal, Pesisir Selatan, West Sumatra, through participant observation over 40 hours across 20 class sessions. Findings identify three dominant patterns: proactive (45%, featuring student-centered methods and Minangkabau cultural integration boosting student engagement by 30%), passive (35%, due to delays and administrative burdens reducing interactions by 40%), and adaptive (20%, hybrid post-pandemic teaching enhancing retention by 35%). Yin's case study approach and Braun-Clarke's thematic analysis confirm influences from internal (motivation) and external (rural infrastructure) factors. Results emphasize Kurikulum Merdeka training for behavioral transformation, supporting inclusive elementary education quality